Deliberative Democracy Practice In Kasepuhan Gelar Alam As A Distinctive Form Of Democracy In Indonesia - Rudiana Rudiana; Muhammad Younus (Politicon : Jurnal Ilmu Politik, 2026)
This study examines the practice of deliberation in Kasepuhan Gelar Alam indigenous community as a culturally embedded form of deliberative democracy in Indonesia. While indigenous governance is often characterized by hierarchical or hereditary authority structures, this article addresses the apparent tension between monarchical leadership and participatory decision-making processes. Drawing on the theoretical framework of deliberative democracy, this research aims to analyze how deliberative practices are institutionalized and negotiated within a customary political system. The research method used a descriptive qualitative research method. The data collection was done through interviews and documentation. The results show that deliberation is institutionalized through forum such as sarasehan and ritual processes surrounding Seren Taun. The study argues that deliberative democracy in Kasepuhan Gelar Alam operates in a contextualized form, where hierarchy and deliberation coexist and mutually shape one another. Rather than conforming to liberal-democratic assumptions of inclusivity and equality, deliberation is embedded within customary institutions that regulate participation and legitimize outcomes. This finding contributes to literature by demonstrating that deliberative democracy is not a uniform model, but a context-dependent practice shaped by cultural norms and power relations.